Influence of Letter Sound Correspondence on Performance of English Reading in Early Childhood - Chepchumba , Agnes; Limo , Alice; Koross , Rachel (African Journal of Education,Science and Technology (AJEST), 2018)
Letter sound correspondence is the relationship between sounds (phonemes) and letters (graphemes). These connections between the sounds in words and the letters that are used to represent those sounds are referred to as letter sound correspondence. The effect of letter sound correspondence on performance of English reading is highlighted on basis of phonemic awareness and phonological awareness. The objective of this mixed method study was to examine the influence of learners’ ability to correspond letters to their correct sounds on performance of English reading in Grade One. The geographical locale of the study was Keiyo Sub County. Stratified and random sampling techniques were used to select the 26 schools and 78 teachers. Fifty two (52) pupils of Grade One were selected (a boy and a girl) using simple random sampling and assessed. The instruments used were questionnaire for ECDE and Grade One teachers and an EGRA checklist for Grade One learner. Data was analyzed quantitatively and qualitatively. The research results rejected the null hypothesis which stated that there exists no significant relationship between a learner’s ability to correspond letters with their correct sound and performance of English reading in Grade One. This was interpreted to mean that pupils need to be taught letter sound correspondences as it will improve their ability to read English. Given the importance of letter sounds in learning to read, this study recommends that preschool teachers be adequately prepared in phonemic and phonological awareness for sustainable development.